An audit of maternal near-miss and mortality cases in a tertiary care rural teaching hospital in Eastern India: A 2-year retrospective analytical case–control study - Nishat Parveen Begg,; Subhankar Dasgupta,; Swarup Chowdhury, (Asian Journal of Medical Sciences, 2022)
Background: Maternal near-miss and mortality patients provide firsthand knowledge of remote and immediate factors linked to morbidity and mortality. Aims and Objectives: The objectives of this study were to evaluate the characteristics of maternal near-miss and mortality cases in a tertiary care hospital. Materials and Methods: The present study is a retrospective analytical case–control study analyzing the different factors associated with maternal near-miss and mortality and comparing the same with a control group having mothers with normal outcome. Data were obtained from record section of Rampurhat Medical College from January 2019 to December 2020. Results: During the study period, maternal mortality ratio was 223 and near-miss cases were 501/lakh live births. Critical care unit admission rate was 2.1% of the total admitted obstetric cases. The maternal near-miss mortality ratio was 2.25. Most women in our study group were anemic teenagers or multigravidas from rural areas with poor educational status and irregular antenatal check-ups as compared to the control group. The most common primary diagnosis in the near-miss group was obstetric hemorrhage (47.47%), while in the mortality group was eclampsia and pre-eclampsia (29.5%), obstetric h emorrhage (20.45%), and heart disease (15.9%). About 81.8% of the participants in the study group had fulfilled the near-miss criteria at the time of admission itself, while 4.5% were brought dead. Conclusion: The underlying risk factors have to be corrected. There should be strict screening protocols from first antenatal visit itself, and earlier referral to higher centers.